Enhancing Arabic Reading and Writing Skills of SMK Muhammadiyah 6 Donomulyo Students through the Think-Pair-Share Strategy - Ulfa Afifa Widyastuti; Mohammad Ahsanuddin; Ibnu Samsul Huda (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study tries to analyze the effectiveness of the Think-Pair-Share strategy in improving the reading and writing skills of Arabic for the students of the eleventh grade at SMK Muhammadiyah 6 Donomulyo. TPS is a cooperative learning strategy where active learning by students is elicited through participation in learning. It is expected that with the strategy, students will raise their comprehension through discussion and interaction with their peers. With TPS, the activities of students in the learning process are expected to be improved. This research was conducted to determine the effect of TPS on student proficiency in the Arabic language. In descriptive qualitative data collection, observation analysis, interviews, and document analysis are used. Data analysis used the Miles and Huberman model involving stages of data reduction, data display, and drawing conclusions. Triangulation methods were also undertaken to validate the results of this research, thereby comparing sources of data and the methods of their collection. This enhances accuracy and credibility in findings. The approach allows for an in-depth understanding of the phenomena being studied. It was found that the reading and writing skills of the students drastically improve with the implementation of TPS. Before the strategy was carried out, only 35% of the students met or achieved the minimum competency standard for reading and 40% met it for writing. It rose to 83% and 90% for reading and writing, respectively, upon using TPS. The model favored enhancing student involvemen, interest, and understanding in learning. The findings will help in devising ways of teaching Arabic language and shall serve as a guide to the educators in implementing strategies that are cooperative in nature.